SADvertising: Relationship of Emotional Marketing Campaigns to the Brand Awareness and Purchase Decision of Different Generations - Jaecee Tanaya; Dyanne Digno; James Harvey Langurayan; Irvin Perono (People and Behavior Analysis, 2023)
Emotional marketing campaigns are dominating the internet and television. From the usual rational marketing campaigns, marketing researchers acquire the idea to put dimensions like storytelling, color, music, and image into their advertisements, which are now called SADvertising or emotional marketing campaigns. This paper aims to determine the relationship of emotional marketing campaigns or SADvertising to the brand awareness and purchase decisions of different generations. The target respondents of this study are five (5) different generations, e.g., Baby Boomers, Generation X, Y, Z, and Generation Alpha. The researchers used a self-administered survey questionnaire and gathered data using a stratified random sampling method. An interview is also done to further strengthen the study. A combination of quantitative and qualitative research design enhances the research analysis. The result of the study using the Spearman-Rho Correlation Test shows that the dimension of emotional marketing campaigns is moderately positive purchase decisions and concluded that there is a significant relationship between the dimension of emotional marketing campaigns to brand awareness and purchase decisions of different generations.